Provident Fund for The Informal Sector: A Case Study of The Informal Sector Workers in Kuala Lumpur, Malaysia - Saidatulakmal Mohd, (Kajian Malaysia, 2015)
Workers in the informal sector are known not to have a formal social security retirement scheme to protect them from the loss of income at old age. One of the reasons for this is the difficulty to regulate a common scheme for both the informal and the formal sectors in terms of contributions and benefits. As a result, most informal sector workers depend on informal schemes such as family support, personal savings and loans after their retirement which leaves them vulnerable to poverty. However, through the Employees Provident Fund (EPF) 1Malaysia Retirement Scheme, workers in the informal sector in Malaysia can now save for the future. This paper investigates the acceptance of 400 informal sector workers in Kuala Lumpur towards this scheme; covering three main kinds of workers i.e. service workers, shop and market sales workers; craft and related trade workers; and those in elementary occupations. Acceptance is measured under two situations: (1) perception on the role of old age protection and provident fund; and (2) willingness to contribute to the fund. A variety of contribution values ranging from a low RM10 to a high RM70 together with their expected returns were presented to the respondents. A logit model is employed to estimate the informal sectors workers willingness to contribute to the EPF. The mean value on the perception of old age program estimated by the study is above average. The study found that amount of contribution and savings behaviour of respondents statistically influenced their willingness to contribute in the EPF.